Factors Determining Mortality in Stevens Johnson Syndrome and Toxic Epidermal Necrolysis: A 10 Year Retrospective Analysis from a Tertiary Care Centre in Southern India - Deepthy V Gopinath; Pradeep S Nair (Journal of Clinical and Diagnostic Research)
Introduction: Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are severe cutaneous adverse drug reactions characterised by high fever, widespread blistering exanthema, and atypical target lesions accompanied by mucosal involvement. SJS/TEN ranks among the leading causes of mortality in dermatology. Adequate management of these conditions requires prompt recognition, identification of risk factors and timely intervention. Due to the rarity of these incidents, their mortality rates and the associated factors are less studied. Aim: To determine the factors contributing to mortality in SJS and TEN, as well as, the mortality rate in a tertiary care centre. Materials and Methods: The present single-centre retrospective observational study was conducted in the Department of Dermatology and Venereology, Government Medical College, Thiruvananthapuram, Kerala, India, from November 2022 to May 2023. Data were extracted from the case records of patients diagnosed with SJS/TEN over a period of 10 years, from January 2012 to December 2021. The variables studied included patients’ age, gender, suspected drug, interval between drug intake and onset of symptoms, time interval between the development of the rash and reporting to a healthcare facility, associated co-morbidities, involved Body Surface Area (BSA), duration of hospitalisation, laboratory investigations, and complications, including death. The data were analysed using the trial version of Statistical Package for Social Sciences (SPSS) software version 29.0. A Pearson’s two-sided Chi-square test was utilised to determine the statistical significance of the variables between the survival group and the mortality group. Results: A total of 146 cases of SJS/TEN were analysed, of which the mean±Standard Deviation (SD) age in the survived group was 42.07±16.704 years, while in the mortality group, it was 67.83±7.57 years (p-value=0.003). There were eight cases of mortality (5.48%). The most common drug in both the mortality group and the survival group was phenytoin. There was a statistically significant association between age (p-value=0.003), Hypertension (HT) (p-value=0.002), presentation with vesicles and bullae (p-value=0.002), and mortality. TEN was more likely to cause mortality than SJS (p-value=0.001), and urinary microscopy abnormalities were associated with mortality (p-value=0.04). Conclusion: A low mortality rate of 5.48% was observed in the present study. Older age, hypertension, presentation with vesicles and bullae, and urinary microscopy abnormalities contributed to mortality. Phenytoin was more likely to cause mortality than other drugs. Mortality was higher in TEN compared to SJS.